Directed Technical Change and Pollution Emission: Evidence From Fossil and Renewable Energy Technologies in China - Qu, Fang; Xu, Lei; Zheng, Biao (Frontiers in Energy Research, 2022)
In this paper, we provide a study of the effect of directed technical change in the energy sector on pollution emission. We make an empirical analysis under the framework of the extended stochastic impacts by regression on population, affluence, and technology model and the environmental Kuznets curve hypothesis and employ the patent data onto fossil energy and renewable energy technologies from 2000 to 2015 to match the economic and environmental data of 30 provinces in China. We show that the prerequisite of restraining pollution emission is to transform the direction of energy technical change rather than only increase the magnitude of energy technical change. Furthermore, the direction of energy technical change will set up dissimilar purification effects on different pollutants, which indicates that the path of emission reduction of renewable energy technology is different. Moreover, promoting energy technology cooperation in adjacent provinces can further intensify the effect of directed energy technical change in restraining pollution emission according to the regional features of each area, and formulating targeted environmental policies to change the energy technology from dirty to clean can effectively curb environmental degradation, which is the mechanism to realize the rationalization and transformation of the energy structure.